Agroforestry-Based Land Management in the Food Estate Area of Ria-Ria Village, Pollung District, Humbang Hasundutan Regency, North Sumatra - Rambey, Ridahati; Elfiati, Deni; Delvian (Talenta Publisher, 2022)
Agroforestry is a land use pattern that combines agricultural and forestry crops on the same land with spatial and temporal arrangements. Ria-ria Village, Pollung District, Humbang Hasundutan Regency is one of the villages designated by the government to be one of the Food Estate areas in North Sumatra which is expected to be able to produce quality agricultural products that can be marketed not only locally but also outside the region. The management of this food estate needs an environmentally friendly concept for the sustainability of natural resources and the environment of the village area. Service activities carried out by socializing agroforestry patterns to the Tani Ria Kerja Community Group, planting trees with a hedge plant model around the land. The types of trees planted in this service activity are Avocado (Persea americana) and Suren (Toona sinensis).